Menelusuri Kearifan dan Strategi Kepemimpinan Khulafaur Rasyidin dalam Perspektif Sejarah Islam - Rahmawati, Endang; Kuds, Salsa Bilkis; Rudiana, Rudiana (Indonesian Journal Publisher, 2024)
This article discusses the leadership of the Khulafaur Rashidin, namely the reigns of Abu Bakr, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib, from the appointment of the caliph to the leadership period and the end of the caliphate, using qualitative methods and review paper research. The results of this study indicate that the caliphs considered the best are Abu Bakr for his constancy, Umar for his firmness, Uthman for his success in writing the Quran and the rebellion at the end of his leadership, and Ali for suppressing the rebellion with a strong spirit.